Identification of Single Phase to Ground Faults in Power Distribution Systems with RG Technique - Ranjithkumar; Maruthupandi (Journal of Electrical Engineering and Automation, 2022)
Fault in a power system is an irregular condition that interrupts the stability of the system and causes a high fault current to flow through the power systems and its devices. Single phase to ground fault is an unsymmetrical fault that takes place between any phase of the system and ground. It is the most frequently occurring fault (70%-80%) that happens in the power system. Resonant Grounding (RG) is the proposed approach that reduces a fault current of a single phase to ground fault to a minimum level that is often independent of fault impedance. In this case, the single phase to ground fault current is too small and the typical overcurrent relay does not respond in this circumstance. As a result, a new and improved approach for detecting single phase to ground fault failures in arc suppression coil grounding distribution system with very low fault currents, though the fault impedance is low, is required. The faults are initially detected based on the neutral voltage displacement by a regionalized fault detection technique. The statement is validated by simulating a single phase to ground fault on an IEEE thirteen node test system and the results are presented. Since it employs local voltage and current information to detect power system fault condition, the suggested technique does not require communication between circuit breaker, relays, transformer, transmission lines etc. This approach can be used to a variety of different forms of unsymmetrical faults.